Study on the dynamic response characteristics of roadbed and pavement under the humidity and season factors in the hilly area of Southwest China - Cao, Mingming; Huang, Wanqing; Liu, Guoming; Wu, Zhiyong (Frontiers in Earth Science, 2023)
The environment of the roadbed and pavement often has a significant impact on its dynamic performance. The stability of the strata in the Hilly Area is poor, and long-term complex environmental impacts will cause significant damage to the pavement. This article tests the dynamic response characteristics of semi rigid and inverted asphalt pavement through road load tests, and measures the humidity data of the roadbed during on-site rainfall. In addition, the variation of pore water pressure in the transition layer under the coupling effect of humidity and dynamic load was analyzed, revealing the influence of seasonal factors on the dynamic response of the pavement and roadbed. The test results indicate that the humidity inside the roadbed is greatly influenced by seasonal factors, and the humidity conditions of the roadbed and pavement vary significantly due to differences in measurement point depth, season, and rainfall. Graded crushed stone cushion is beneficial for improving the humidity conditions of the roadbed. The pore water pressure of the graded crushed stone transition layer did not show significant pore water reabsorption throughout the entire loading process. Meanwhile, the thickness of the surface layer and the magnitude of the load have a significant impact on the measurement of pore water pressure in the transition layer. The measured values of the dynamic response indicators of the pavement are greatly influenced by seasonal factors. The research in this article will provide theoretical and guiding significance for the dynamic response characteristics of pavement under the influence of multiple factors in the southwestern hilly area.